Validation of functioning resistant genes against Malaysian biotype of brown planthopper in rice variety, Rathu Heenati - Ab Ghaffar, Mohamad Bahagia; Mohd Yusuf, Ruziah; Mohamad Saad, Maisarah; Mohd Yusof, Muhammad Fairuz; Ab Razak, Shahril; Hashim, Habibuddin; Shaharuddin, Noor Azmi (Friends Science Publishers, 2022)
Rathu Heenati is a donor parent commonly used in the development of resistant rice varieties against brown planthopper (BPH), Nilaparvata lugens, which is a devastating insect pest of rice. The variety is reported to have a broad-spectrum resistance against BPH, through the action of multiple genes and quantitative trait loci (QTL) including Bph3, Qbph3, Qbph4 and Qbph10. The present study was carried out to validate the effectiveness of those genes against Malaysian BPH population. The study was conducted using an F2 segregating population which was obtained from a cross between Rathu Heenati and a Malaysian commercial variety, MR219. Plant damage score was used to estimate the degree of plant tolerance, while the amount of honeydew excretion was used to measure the level of antibiosis. The gene presence in an individual plant was determined based on the segregation pattern of the flanking microsatellite markers of the respective reported genes. Results confirmed the role of Bph3 and the three other QTLs in conferring resistance against the Malaysian biotype of BPH. Marker assisted breeding can facilitate the monitoring of the introgressed genes in the plants of a breeding population.